Institutional equilibrium in EU economies in 2008 and 2018: SEM-PLS models - Mateusz Borkowski (Statistics in Transition new series (SiTns), 2022)
The aim of the research is to identify the strength and direction of the development of the relationship between formal and informal institutions and to assess the institutional equilib- rium of modern economies. The structural equations modelling based on partial least squares (SEM-PLS) is applied to achieve the purpose of the article. It is an econometric method that allows the measurement and analysis of the dependencies between latent vari- ables (measures that cannot be directly observed). The study included 27 EU economies and the research period covered the years 2008 and 2018. The results of the study demonstrate that the quality of informal institutions strongly, positively determines the quality of formal institutions. The conducted analyses indicate that modern economies are diversified in terms of the quality of informal and formal institutions and, consequently, in institutional equilibrium. Considerable institutional disparities also translate into a large diversification in economic development. The article proposes a different meaning of institutional equilib- rium, understood as the achieved state of institutional structure characterised by high quality informal institutions which interact with each other to improve the efficiency of formal in- stitutions. The article presents a comprehensive model of the institutional structure and a unique method of measuring institutional equilibrium.
Keywords: 519; institutional equilibrium; SEM-PLS; economic growth and development